Planned Overkill of Paramour with Cycle Spokes by a Physically Challenged: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
A 35-year-old male was found dead with a metallic wire twisted around his neck and both his eyeballs punctured with metallic probes. The deceased was killed as a revenge for having illicit relationship with a neighbouring woman. At autopsy, the weapons were found in situ on the neck and the eyeballs. The case highlights the gruesomeness of the overkill murder with description of atypical injuries, which were produced by the unique hand-made weapons. The paper highlights the preparedness of the accused and the postmortem findings along with the photographs, owing to its rarity.
Keywords: Overkill murder,; Cycle spoke; Strangulation,; Eyeball puncture